2017
DOI: 10.21082/jhort.v27n1.2017.p45-54
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Produksi dan Mutu Benih Wortel (Daucus carota) Varietas Lokal Melalui Pemangkasan Cabang dan Pemupukan Boron

Abstract: ABSTRAK.Teknik perbenihan perlu diperhatikan untuk mendapatkan benih wortel bermutu. Hal ini terjadi dikarenakan oleh teknik perbenihan / pemilihan umbella sebagai sumber bibit kurang tepat. Penelitian bertujuan untuk meningkatkan produksi dan mutu benih wortel melalui perlakuan pemangkasan cabang dan pemberian pupuk boron. Penelitian dilakukan pada bulan JanuariMei 2014 di Kebun Percobaan Berastagi, dengan ketinggian ± 1.340 m dpl, jenis tanah Andisol. Rancangan yang digunakan adalah rancangan acak kelompok f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Huang, et al, reported similar facts that the addition of N from the marketwaste liquid organic fertilizer resulted in a higher chlorophyl concentrations in leaves which in turn, promote photosynthesis and canopy formation [7]. It was added by Marpaung et al, that liquid organic fertilizer is bale to increase the vigority of plants, as ar esult, the plants become strong and the leaf canopy becomes wider [12].…”
Section: Canopy Of Setariamentioning
confidence: 91%
See 1 more Smart Citation
“…Huang, et al, reported similar facts that the addition of N from the marketwaste liquid organic fertilizer resulted in a higher chlorophyl concentrations in leaves which in turn, promote photosynthesis and canopy formation [7]. It was added by Marpaung et al, that liquid organic fertilizer is bale to increase the vigority of plants, as ar esult, the plants become strong and the leaf canopy becomes wider [12].…”
Section: Canopy Of Setariamentioning
confidence: 91%
“…The usage of liquid fertilizer according to Budiraharjo et al, in an effort to utilize organic wastes has a potent to be applied in the fields [11]. According to Marpaung et al, the differences between traditionalmarket-waste organic compost to that of liquid is, the minerals from the compost need time space in order the minerals to be available to plants, on the contrary, those of liquid fertilizer, the minerals are available as soon as the fertilizer is applied to the soil [12]. It is reported by Hanolo that the decomposition process of compost causes the late availability of its minerals [13].…”
Section: The Heights Of Setaria Grassmentioning
confidence: 99%
“…While the productivity rate of carrots in Karo has not achieved a similar level shown in European countries, the potential is to improve by the recent successes in seed technology development. Quality local seeds yielded significantly higher and produced competitive carrot quality [19].…”
Section: Carrot Postharvest Losses and Supply Chainmentioning
confidence: 97%
“…Keberhasilan produksi dan kualitas benih ditentukan oleh beberapa faktor. Faktor yang mempengaruhi kualitas benih antara lain lingkungan tumbuh tanaman cahaya, suhu, dan kelembapan (Kantolic & Slafer 2007), zat pengatur tumbuh (Mohanta et al 2015), polinasi, populasi serangga penyerbuk (Gaffney et al 2011), dan teknik pemangkasan cabang serta unsur hara (Marpaung et al 2017). Proses terbentuknya benih berasal dari hasil polinasi.…”
Section: Pendahuluanunclassified